Implementation of Digital Children's Fashion Design Video Tutorials Based on the Sketchbook Application for Fashion Design Skills Students at MAN 3 Tulungagung Phase F Program - Afanita, Akmalia; Yuniati, Mita; Marniati, Marniati (Universitas Syiah Kuala, 2025)
This study aims to determine the application of digital children's fashion design tutorial videos based on the sketchbook application for phase F students of the fashion design skills program at MAN 3 Tulungagung. This study uses a qualitative descriptive approach with a pre-experimental type (one shot case study). The research subjects consisted of 18 grade XI students of Phase F of the Fashion Design Skills Program. Data were obtained through validation by media experts and material experts, as well as assessment of student design results. Data analysis included analysis of media feasibility based on validation results, and analysis of psychomotor learning outcomes. The results showed that the results of validation of the media aspect by three validators obtained an average of 85.4% and the material aspect was 89.4%, both of which were included in the very good category. The video was assessed to meet the criteria for appearance, audio, visuals, and relevance of learning materials. The application of this media showed complete student learning outcomes, with a percentage of 100% on the cognitive test and 89% on the psychomotor test. Thus, the Sketchbook-based video tutorial is feasible and effective for use as a digital fashion design learning medium.